Synthesis, Characterization of Cellulose Modified with 2-Mercaptobenzothiazole and Its Adsorption To Cu(II) Ion in Aqueous Solution - Ahmad Fatoni; Soerja Koesnarpadi; Nurlisa Hidayati (Universitas Gadjah Mada, 2015)
The modification of cellulose with 2-mercaptobenzhotiazole (MBT) through grafting and impregnating methods has been done. Modified cellulose used as adsorbent for Cu(II) ion in aqueous solution. The aims of research were modification cellulose with 3-chloropropyltrimethoxysilane and 2-mercaptobenzhotiazole (MBT), characterization of the modified cellulose with FTIR, SEM and XRD and adsorption study between cellulose-MBT adsorbent with Cu(II) ion in aqueous solution. The adsorbent of cellulose-MBT was synthesized by reflux process. Adsorption study between cellulose-MBT adsorbent with Cu(II) ion was investigated based on influence of pH solution, interaction time and initial concentration of Cu(II) ion. The result showed that activated cellulose can be modified with MBT to become cellulose-MBT adsorbent. The functional group of –C=N appeared at wavenumber 1658 cm-1 attributed to functional group of -C=N- is Schiff base of MBT. Presence functional group of S-H at cellulose-MBT adsorbent was not detected. The surface morphology of cellulose-MBT adsorbent after being interacted with Cu(II) ion was different before being interacted with Cu(II) ion. The diffractogram of cellulose-MBT adsorbent has similarity with cellulose-MBT adsorbent-Cu(II) ion. The optimum adsorption of Cu(II) ion was observed at pH 7.0 and 150 min of interaction time. Percentage of Cu(II) ion was absorbed by cellulose-MBT adsorbent tended to be constant after Cu(II) ion concentration 100 ppm.